From “immune silence” to “immune dialogue”: modification strategies for bone substitutes based on bone immunomodulatory characteristics - Zhao, Jiaming; Sun, Quan; Gu, Jing; Xu, Xiaofan; Xia, Minghui; Xia, Haibin; Zhao, Zifan (Frontiers in Cell and Developmental Biology, 2025)
Traditional bone substitute materials primarily employ a strategy centered on the direct modulation of osteoblast differentiation. However, this strategy, to some extent, overlooks the pivotal regulatory role of the immune microenvironment in the process of bone regeneration. With the continuous advancement of bone biology research, the significant regulatory role of the immune microenvironment in the osteogenic process has gradually been substantiated. Osteoimmunology studies reveal that immune cells dynamically coordinate the osteoblast-osteoclast balance through shared signaling networks. The “immune-silent” characteristic of traditional bone substitute materials often leads to fibrous encapsulation and failure of osseointegration at the surgical site. Conversely, the research focus of the new generation of bone substitute materials is centered on dynamic immune interaction strategies: by optimizing surface topology to guide macrophages toward a reparative polarization; leveraging the temporal release of bioactive ions to precisely regulate the balance between inflammation and regeneration; and integrating intelligent response systems to dynamically adapt to changes in the pathological microenvironment. Through the synergistic effects of these multifaceted approaches, the ultimate goal is to effectively promote bone tissue regeneration. Against this backdrop, this paper proposes a transition strategy from “immune silence” to “immune dialogue,” which emphasizes the active and effective modulation of immune responses through meticulous material design, thereby reshaping the bone microenvironment to create favorable conditions for bone tissue repair and reconstruction. This innovative concept breaks through the limitations of traditional unidirectional osteogenic modulation, successfully establishing a two-way dialogue bridge between bone substitute materials and the immune system, significantly improving the efficiency of clinical bone defect repair, while also greatly enhancing patient satisfaction. This review systematically outlines the latest advancements in the fields of osteoimmunology and biomaterials, focusing on the key scientific issue of “osteogenic differentiation regulated by the osteoimmune microenvironment,” and provides an in-depth analysis of biomaterial design strategies based on the dynamic balance of the immune microenvironment. The aim is to elucidate the immune-metabolic modulation mechanisms mediated by materials, thereby enhancing the clinical translation efficacy of biomaterials, and provide theoretical support and technical pathways for the precise repair of bone defects.